Efforts to Improve the Fourth-Grade Elementary Students’ Learning Outcomes Using Audio Visual Media-Assisted Scientific Learning Models - Sunrais Josua Saragih; Patri Janson Silaban; Rumiris Lumban Gaol (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper examines the improvement of students’ learning outcomes by using the scientific learning model assisted by audio-visual media and determines the process of implementing the scientific learning model assisted by audio-visual media in class IV at SD Negeri 116906 in the academic year 2022/2023. The research method used in this research is classroom action research. The research subjects consisted of 26 students. Based on the analysis and discussion of the research, the learning outcomes in individual student pre-tests were five students who completed the classical test, which indicates 17% with an average score of 46.5. In cycle I, 13 students individually completed the results with a classical score of 43% and an average score of 60.76. In cycle II, 25 students individually completed the results with a classical score of 83% and an average score of 79.8. It shows that in cycle I to cycle II there was an increase. Based on the result of learning implementation using the scientific learning model assisted by audio-visual media, teacher activity observation in cycle I was 62% in the sufficient category and in cycle II it increased to 88% in the very high-quality category. Meanwhile, the results of student activity observation in cycle I indicated 66% in the sufficient category and in cycle II it increased to 86% in the good category. Thus, the scientific learning model assisted by audio-visual media can improve students’ learning outcomes.